POTENTIAL FOR TAX AVOIDANCE BASED ON PROFITABILITY, LEVERAGE, AND COMPANY SIZE IN INDONESIA’S MINING INDUSTRY - Tesniwati, Rini (Jurnal Pajak dan Keuangan Negara (PKN), 2026)
Tax avoidance in countries where taxes is the primary source of state revenue, while the potential for tax collection remains significant, must be taken preemptive efforts to secure the state's rights.This study will assess and investigate the impact of profitability, leverage, and firm size on the possibility for tax avoidance, with a focus on mining enterprises. Purposive sampling strategies were used to select the sample from eight significant mining corporations. The ordinary least squares approach for statistical data analysis, specifically estimating its correlation with the effective tax rate as a proxy for tax avoidance. The argument was then supported by numerous related research. The outcomes of this study, in addition to statistically assessing determining elements, indicate strategic actions for fiscal policy input, as well as suggestions for other researchers to explore the logistics sector.